Non-bone-derived exosomes: a new perspective on regulators of bone homeostasis - Ping Wang; Wenkai Shao; Zilin Li; Bo Wang; Xiao Lv; Yiyao Huang; Yong Feng (Cell Communication and Signaling, 2024)
Abstract Accumulating evidence indicates that exosomes help to regulate bone homeostasis. The roles of bone-derived exosomes have been well-described; however, recent studies have shown that some non-bone-derived exosomes have better bone targeting ability than bone-derived exosomes and that their performance as a drug delivery vehicle for regulating bone homeostasis may be better than that of bone-derived exosomes, and the sources of non-bone-derived exosomes are more extensive and can thus be better for clinical needs. Here, we sort non-bone-derived exosomes and describe their composition and biogenesis. Their roles and specific mechanisms in bone homeostasis and bone-related diseases are also discussed. Furthermore, we reveal obstacles to current research and future challenges in the practical application of exosomes, and we provide potential strategies for more effective application of exosomes for the regulation of bone homeostasis and the treatment of bone-related diseases. Video Abstract